FABRICATION OF CARBON–POLYMER COMPOSITE BIPOLAR PLATES FOR POLYMER ELECTROLYTE MEMBRANE FUEL CELLS BY COMPRESSION MOULDING - Raza, M. A.; Ahmed, R.; Saleem, A.; Din, R. U. (The Nucleus, 2020)
Fuel cells are considered as one of the most important technologies to address the future energy and environmental pollution problems. These are the most promising power sources for road transportation and portable devices. A fuel cell is an electrochemical device that converts chemical energy into electrical energy. A fuel cell stack consists of bipolar plates and membrane electrode assemblies (MEA). The bipolar plate is by weight, volume and cost one of the most significant components of a fuel cell stack. Major functions of bipolar plates are to separate oxidant and fuel gas, provide flow channels, conduct electricity and provide heat transfer. Bipolar plates can be made from various materials including graphite, metals, carbon / carbon and carbon/polymer composites. Materials for carbon–polymer composites are relatively inexpensive, less corrosive, strong and channels can be formed by means of a moulding process. Carbon– polymer composites are of two type i. e; thermosetting and thermoplastic. For thermosetting composite a bulk molding compound (BMC) was prepared by adding graphite, vinyl ester resin, methyl ethyl ketone peroxide and cobalt naphthalate. The BMC was thoroughly mixed, poured into a die mould of a bipolar plate with channels and hot pressed at a specific temperature and pressure. A bipolar plate was formed according to the die mould. Design of the mould is also discussed. Conducting polymers were also added to BMC to increase the conductivity of bipolar plates. Particle size of the graphite has also a significant effect on the conductivity of the bipolar plates. Thermoplastic composites were also prepared using polypropylene and graphite.